The Forests of Coorg State - Trimurti, N. (Indian Forester, 1955)
The State of Coorg is located on the eastern slops of western ghats, the elevation varying mostly from about 2,000 to 5,000 feet. It slopes gently on the eastern side and steeply on the western. The rainfall varies from about 30 inches in some tracts adjoining Mysore State, to about 250 inches in some tracts on the western ghats. The forest type is very varied and can be divided into three definite zones depending on the rainfall. In the ghat forests with very high rainfall the forest is of the tropical wet evergreen type. In the region of 50 inches to 100 inches rainfall the moist deciduous type of forest occurs, and in the region of 30 inches to 40 inches rainfall there is the dry deciduous type. In the first zone of heavy rainfall evergreen species are found and the forests are magnificent, the trees being over 100 feet in height and reaching up to 20 feet and more in girth. In the moist deciduous zone very valuable teak of very good quality as well as rosewood of very fine colour and beauty occur, and in the dry deciduous zone sandalwood is found. The evergreen forests can produce about 8 lacs cubic feet of evergreen timber per year. The moist deciduous zone produces about 7 lacs cubic feet of hardwoods including teak, rosewood, etc. The dry deciduous forest produces about 100 tons of sandalwood per year. The natural regeneration in the evergreen forests is good. In the moist deciduous zone artificial regeneration by clear-felling and planting with teak is being carried out. The total gross forest revenue of the State is about 40 lacs of rupees and the expenditure is about 12Â½ lacs of rupees and the net forest revenue is about 27Â½ lacs of rupees.